Gemology from science to art: An exposition as an extensionist action, promoting new pedagogical practices in the gemology course - Bomfim, Shelley; Dutra de Magalhães, Marcus Vinícius; Bastos Depianti, Janaina (Guará Journal, 2019)
In search of new pedagogical practices and breaking paradigms, faced with the challenges of the academic world, an opportunity arose for students of the Gemology program at UFES, a pioneering and unique program in Brazil, to bring to the general public an approach aimed at sparking reflection, recreating actions with new perspectives, and improving strategies. In this sense, the exhibition: "Gemology from Science to Art" was conceived and developed as part of the extension project "Garimpando a Arte" (Garimpando a Arte) with the objective of presenting the aspects of the Gemology program from a scientific, social, and artistic perspective outside of a formal setting. The exhibition lasted 44 days at the UFES Central Library with 2,082 visitors, reaching a record attendance for this type of exhibition in the space in question. The 53 exhibitors, called "gemoartists," were able to present their work in a unique way and using free techniques, presenting a large collection of works on minerals and their potential. Thus, the applied methodology proved to be effective in achieving its objectives, as it promoted culture within the academic space and in the city of Vitória, contributing to increasing the visibility of the Bachelor’s Degree in Gemology, in addition to publicizing the great gemological potential of the state of Espírito Santo.